MOTIVATION AND CREATIVITY INFLUENCE TOWARD STUDENTS ACADEMIC - Azima Dimyati; Agus Purnomo (International Conference On Law, Business and Governance (ICon-LBG), 2016)
This research is intended to identify and analize motivation and creative competence in improving students academic result. In addition, It is also aimed to build and develop creativity and motivation to the improvement of students academic result. Variables used in this research are creativity, motivation, and academic result.Population in this research is students from Law and Social Science Faculty who are active in even semester. There are 512 students from Law and Social Science Faculty in academic year of 2016/2017. Data source taken in this research are 77 repondents. This research data uses primary data which was gotten from quesionare. Analysis method that is used to examine hypotheses in this research, is double linear regression. Data gotten is then analyzed by using SPSS.This research result shows that motivation and creativity have impact to students academic result at Political and Social Science Faculty in Bandar Lampung University both partially and fully.